2017
DOI: 10.1111/1462-2920.13640
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial harmful algal blooms are a biological disturbance to Western Lake Erie bacterial communities

Abstract: Human activities are causing a global proliferation of cyanobacterial harmful algal blooms (CHABs), yet we have limited understanding of how these events affect freshwater bacterial communities. Using weekly data from western Lake Erie in 2014, we investigated how the cyanobacterial community varied over space and time, and whether the bloom affected non-cyanobacterial (nc-bacterial) diversity and composition. Cyanobacterial community composition fluctuated dynamically during the bloom, but was dominated by Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(140 citation statements)
references
References 69 publications
(84 reference statements)
7
123
3
Order By: Relevance
“…Despite these limitations, phycosphere community composition remained representative of heterotrophic bacteria associated with blooms of M. aeruginosa . For example, two of the three most abundant heterotrophic taxa across our isolate collection, P. bacilliformis and Cytophagaceae (Table ), are strongly associated with blooms of M. aeruginosa (Tanabe et al, ; Berry, Davis, et al, ). We had hypothesized that the phycosphere could facilitate survival of a streamlined host with atypical nutrient requirements caused by gene loss, for example the loss of key genes for amino acid biosynthesis in LL/LG isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, phycosphere community composition remained representative of heterotrophic bacteria associated with blooms of M. aeruginosa . For example, two of the three most abundant heterotrophic taxa across our isolate collection, P. bacilliformis and Cytophagaceae (Table ), are strongly associated with blooms of M. aeruginosa (Tanabe et al, ; Berry, Davis, et al, ). We had hypothesized that the phycosphere could facilitate survival of a streamlined host with atypical nutrient requirements caused by gene loss, for example the loss of key genes for amino acid biosynthesis in LL/LG isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses were carried out in R version 3.2.1 using phyloseq (61), vegan (62), and custom functions written by Michelle Berry (63). All figures were generated using the ggplot2 R package (64).…”
Section: Methodsmentioning
confidence: 99%
“…Actinobacteria and Bacteroidetes were induced a sharp decrease and increase crossing the change point along the gradient of the agricultural area. how the cyanobacterial community varied over space and time, and whether the bloom affected non-cyanobacterial (nc-bacterial) diversity and composition [24]. In the study, extracted DNA was amplified using primer set 515f/806r, which targets the V4 hypervariable regions of the 16S rRNA gene.…”
Section: Environmental Variables and The Microbial Community Structuresmentioning
confidence: 99%
“…The most of the lakes examined in this section 4 were associated with this genus. Lake Taihu has experienced Microcystis bloom events for decade, Xie et al [10] and Steffen et al [21] focused their studies on this lake; Cao et al [14] reported that analysis at the genus level of Cyanobacteria identified that Microcystis was among the most abundant genus in the 21 plateau lakes in Yunnan, China; Steffen et al [21] stated that Microcystis-dominated blooms had been observed in the western basin of Lake Erie annually since the 1990s; the study by Berry et al [24] in western Lake Erie also showed that Cyanobacterial community composition fluctuated dynamically during the bloom, but was dominated by Microcystis and Synechococcus OTUs; Tromas et al [25] reported that blooms in their study site (Lake Champlain, North America) tended to be dominated by one or two genera of cyanobacteria: Microcystis or Dolichospermum; in the study of Touzet [19] …”
Section: Microcystis Appears In Most Of the Studies Lakesmentioning
confidence: 99%